2018
DOI: 10.3802/jgo.2018.29.e65
|View full text |Cite
|
Sign up to set email alerts
|

A triage strategy in advanced ovarian cancer management based on multiple predictive models for R0 resection: a prospective cohort study

Abstract: ObjectiveTo present the surgical outcomes of advanced epithelial ovarian cancer (AEOC) since the implementation of a personalized approach and to validate multiple predictive models for R0 resection.MethodsPersonalized strategies included: 1) Non-invasive model: preoperative clinico-radiological assessment according to Suidan criteria with a predictive score for all individuals. Patients with a score 0–2 were recommended for primary debulking surgery (PDS, group A), or otherwise were counseled on the choices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
(56 reference statements)
1
30
1
2
Order By: Relevance
“…There are limited data on aetiology, diagnosis, prognostic factors and treatment of OCS. However, studies concluded that prognostic factors and treatment of carcinosarcomas are associated with epithelial components, as carcinosarcomas are carcinomas with epithelial–mesenchymal transition and heterologous differentiation [ 1 , 4 , 6 , 20 , 21 , 22 , 23 , 24 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Adhesion between the small bowel and the abdominal aorta leading to obstructive ileus is a possible complication after para-aortic lymph node dissection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited data on aetiology, diagnosis, prognostic factors and treatment of OCS. However, studies concluded that prognostic factors and treatment of carcinosarcomas are associated with epithelial components, as carcinosarcomas are carcinomas with epithelial–mesenchymal transition and heterologous differentiation [ 1 , 4 , 6 , 20 , 21 , 22 , 23 , 24 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Adhesion between the small bowel and the abdominal aorta leading to obstructive ileus is a possible complication after para-aortic lymph node dissection.…”
Section: Resultsmentioning
confidence: 99%
“…However, the definition of optimal cytoreduction has changed over the years. Currently, optimal cytoreduction is defined as no macroscopic residual disease [ 29 ]. Although the role of cytoreduction in ovarian carcinoma is well established, some studies have reported no benefit of cytoreduction in OCS [ 4 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fagotti et al and Feng et al concluded that preoperative laparoscopic staging is useful in making decisions about primary debulking surgery. [28,29]…”
Section: Discussionmentioning
confidence: 99%
“…Since 2015, the specialized ovarian cancer unit at our institution has implemented a personalized surgical approach for the treatment of OC patients ( 7 ). We adopted two-tier predictive models for R0 resection; specifically, a preoperative clinic-radiological assessment for all OC patients and a laparoscopic assessment, when necessary.…”
Section: Introductionmentioning
confidence: 99%